Analysis of stress in the walls of simulated artificial root canals during instrumentation with Reciproc system: a pilot study using a photoelastic model - Vilela, Ana Elisa; Raldi, Denise Pontes; Cardoso, Flavia Goulart Rosa; Claro, Cristiane Aparecida de Assis; Habitante, Sandra Márcia (Brazilian Dental Science, 2016)
Objective: The aim of this pilot study was to perform in vitro analysis of the stress related to instrumentation of artificial root canals with Reciproc System by using the photoelasticity method. Material and Methods: Photoelastic models consisted of two epoxy resin blocks simulating root canals, which were attached with cyanoacrylate adhesive to a base and placed at the centre of a circular polariscope in a dark-field configuration. The Reciproc R25 instrument was mounted to a VDW motor and used in block 1 up to 12 mm (working length) and then the same instrument was used in block 2. The images were captured by video camera and analysed at the time of the fourth penetration. Isochromatic fringes were observed in the cervical, middle and apical thirds at mesial and distal regions of each block. Therefore, they were divided into cervical-mesial (CM), cervical-distal (CD), middle-mesial (MM), middle-distal (MD), apical-mesial (AM) and apical-distal (AD). Results: In the first instrumentation, it was found that the greatest stress occurred at the middle-distal region (1.38), followed by middle-mesial (1.20), apical-distal (1.20) and apical-mesial regions (1.20). In the second instrumentation, the greatest stress occurred at the middle-mesial (1.20), apical-distal (1.20), apical-mesial (1.20) and middle-distal regions (0.90). Conclusion: The greatest stress occurred in the middle and apical thirds during the first instrumentation. Re-utilization caused less stress. KeywordsDental Stress Analysis; Endodontic; Instrumentation.